Genetically determined reproductive aging and coronary heart disease: a bidirectional 2-sample mendelian randomization - Dam, Veerle; Onland-Moret, N Charlotte; Burgess, Stephen; Chirlaque, Maria-Dolores; Peters, Sanne A E; Schuit, Ewoud; Tikk, Kaja; Weiderpass, Elisabete; Oliver-Williams, Clare; Wood, Angela M; Tjønneland, Anne; Dahm, Christina C; et al. (The journal of clinical endocrinology & metabolism, 2022)
Accelerated reproductive aging, in women indicated by early natural menopause, is associated with increased coronary heart disease (CHD) risk in observational studies. Conversely, an adverse CHD risk profile has been suggested to accelerate menopause.To study the direction and evidence for causality of the relationship between reproductive aging and (non-)fatal CHD and CHD risk factors in a bidirectional Mendelian randomization (MR) approach, using age at natural menopause (ANM) genetic variants as a measure for genetically determined reproductive aging in women. We also studied the association of these variants with CHD risk (factors) in men.Two-sample MR, using both cohort data as well as summary statistics, with 4 methods: simple and weighted median-based, standard inverse-variance weighted (IVW) regression, and MR-Egger regression.Data from EPIC-CVD and summary statistics from UK Biobank and publicly available genome-wide association studies were pooled for the different analyses.CHD, CHD risk factors, and ANM.Across different methods of MR, no association was found between genetically determined reproductive aging and CHD risk in women (relative risk estimateIVW = 0.99; 95% confidence interval (CI), 0.97-1.01), or any of the CHD risk factors. Similarly, no associations were found in men. Neither did the reversed analyses show evidence for an association between CHD (risk factors) and reproductive aging.Genetically determined reproductive aging is not causally associated with CHD risk (factors) in women, nor were the genetic variants associated in men. We found no evidence for a reverse association in a combined sample of women and men.
Gesehen am 09.01.2024